A Customer-Oriented Approach to Satisfaction with Public Service Providers. Empirical Findings from a Market Undergoing Liberalization - Dan Cristian DABIJA; Raluca BĂBUŢ (COMIATI); Ciprian Marcel POP (Transylvanian Review of Administrative Sciences, 2013)
Unlike the open competition economic sectors where tens, hundreds or even thousands of companies ‘struggle’ to provide consumers not only with services but also with special utility, the regulated markets (power supply, public transportation, public safety etc.) are dominated by a limited number of service providers. Sometimes the situation is pushed to the point where a few companies ‘control’ the market and set the prices. Although the power and gas supply is still ‘dictated’ by the Romanian authorities, the directives of the European Union coerce the government to deregulate the utility sector and liberalize prices. For the companies concerned, this entails a better customer orientation and an adaptation of their services to the customers’ expectations and preferences. From this point forward, the utility suppliers will have to better cope with the public’s various forms of dissatisfaction with prices, performance or communication etc. The authors of the current paper attempt to analyze how some characteristics of the marketing mix of utility providers may contribute to a proper understanding and building satisfaction with two surveyed regional providers. The findings reveal significant management implications which help utility providers better channel their efforts into the proper knowledge of markets and particularly the target segments that they approach.